Six- to eight-year-olds’ performance in the Heart and Flower task: Emerging proactive cognitive control - Roebers, Claudia M. (Frontiers in Psychology, 2022)
The Heart and Flower task is used worldwide to measure individual differences in executive functions and/or cognitive control across a wide age range. The task reliably maps individual differences and these have consistently been found to be predictive for different aspects of school readiness and academic achievement. The idea has been put forward that there is a developmental shift in how children approach such a task. While 6-year-olds tend to adapt their task strategy ad hoc and reactively, older children increasingly engage in proactive cognitive control. Proactive cognitive control entails finding the right response speed without risking errors, always dependent on the cognitive conflict. In the present contribution, children's adjustment of response speed was addressed in a large sample with three age groups (N = 106 6-year-olds with a mean age of 6 years; 3 months; N = 108 7-year-olds with a mean age of 7 years; 4 months; N = 78 8-year-olds with a mean age of 8 years; 1 month). Response speed adjustments and the development thereof were targeted both across the Flower and Mixed blocks, respectively, and within these blocks focusing on errors and post-error slowing. Results revealed evidence for a developmental shift towards more efficient proactive cognitive control between 6 to 8 years of age. At the same time, we found that even the youngest age group has emerging proactive cognitive control skills at their disposal. The present study thus tracks the early roots of later efficient executive functions and cognitive control, contributes to a better understanding of how developmental progression in cognitive control is achieved, and highlights new avenues for research in this domain.